A study on the factors affecting the stable isotopiccomposition in precipitation of Tamil Nadu, India - Chidambaram, S.; Prasanna, Mohan Viswanathan; Ramanathan, A.; Vasu, K.; Shahul Hameed, A.; Warrier, U.; Srinivasamoorthy, K.; Manivannan, R.; K, Tirumalesh; P, Anandhan; G, Johnsonbabu (John Wiley and Sons Ltd, 2009)
Stable isotope measurements in precipitation help us to form the basic inference about the origin and the state of water in different environments. The precipitation samples collected during the South West Monsoon (SWM) during August 2007 from 37 different locations in the state help in deriving the first preliminary local meteoric water line (LMWL) for the Tamil Nadu State. The study reveals that there are three main sources of water vapours, namely South East Arabian Sea (SEAS), Indian Ocean (IO) and evaporation from local water bodies. There are wide variations in the altitude and amount of rainfall received in the state. It is also noted that there is a significant variation in the latitude and the distance from the coast. Hence, an attempt is made in this paper to study the factors controlling the composition of stable isotopes in precipitation with reference to amount of rainfall, latitude, altitude and the continental effect. The altitude and continental effect shows good correlation to the variations in stable isotope composition.